Wybrane problemy przygotowania i realizacji lokalnych strategii rozwoju zrównoważonego (na przykładzie gmin i społeczności lokalnych regionu wałbrzyskiego) - Czaja, Stanisław; Becla, Agnieszka (Chosen Problems of Preparing and Rrealizing of Local Sustainable Development Strategies (for Instance Communies and Local Societies of the Wałbrzych Region), 2007)
The article presents chosen problems of preparing and realizing of local sustainable development strategies. The analysis was carrying out for the Wałbrzych region for the 41 communities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 164-183